Correlation of the anthropometric characteristics and the ability to jump in volleyball - D'Isanto, T.; Di Tore, P. A.; Altavilla, G. (Journal of Human Sport & Exercise, 2018)
Volleyball is a sport of situation classified among the activities with an alternate aerobic - anaerobic commitment, which requires a high use of large muscular masses, with an accentuated prevalence of the anaerobic alactacid metabolism. The purpose of this work is to analyze and evaluate the correlations between the various variables of an anthropometric and functional nature, studied by testing a population of high-level volleyball players (Under 20 elite), subdividing them according to the role it occupied inside the group. The study was carried out on 42 volleyball players divided into four groups. In all subjects the following anthropometric parameters were assessed: height, weight, body mass index (BMI), height with a stretched arm (AH1) and height with two extended arms (AH2). The indirect measurement of the explosive force was carried out with the Bosco method: squat jump (SJ), counter movement jump (CMJ), CMJ with the use of the arms (CMJas). The elevation and coordination skills were assessed with the Vertec test using the technical gesture of the attack (Vertec attack, VA) and the wall (Vertec wall, VW). Other data can be obtained by evaluating the results obtained by the difference between the measurement of the Vertec attack (VA) and the height with a stretched arm (AH1) and between that of the Vertec wall (VW) and the height with two outstretched arms (AH2). The results of the anthropometric parameters showed significant differences in height (F = 4.7; p <0.006), height with a stretched arm AH1 (F = 3.5; p <0.02) and height with two outstretched arms AH2 (F = 3.5; p <0.02). In the comparison by role we did not obtain any statistical significance regarding the Bosco test. A high correlation was found between the results of the anthropometric parameters and those of the Vertec. The results show that in high-level youth volleyball, the athletes' anthropometric profile is directly linked to variables that must be used for the selection of talents and for training planning.